Nutrient and water management for bell pepper (Capsicum annuum) production: A study on drip irrigation in silty loam soils - VIKAS SHARMA; NITIN M CHANGADE (The Indian Journal of Agricultural Sciences)
The study demonstrates that both surface and subsurface drip irrigation combined with nitrogen fertigation significantly enhanced plant growth, fruit yield, and water use efficiency (WUE) of bell pepper compared to the control. In the selected study area, subsurface drip irrigation (SSDI) improved bell pepper fruit yield by 16.5% compared to surface drip irrigation (SDI). The most effective approach for water and nitrogen management was identified as irrigation at 85% of crop evapotranspiration combined with 85% of the recommended nitrogen dose under SSDI, achieving significant gains in fruit yield and WUE. Furthermore, SSDI demonstrated the potential to save 15% of irrigation water and 15% of the recommended nitrogen dose while maintaining comparable crop productivity to SDI. These findings illuminate the transformative potential of subsurface drip irrigation (SSDI) for bell pepper cultivation in the Indian Punjab. By conserving precious freshwater resources and curtailing nitrogen overuse inherent in traditional broadcasting methods. SSDI exemplifies sustainable agriculture, enhancing crop productivity while conserving freshwater and reducing nitrogen overuse. Its adoption offers a resource-efficient solution for bell pepper cultivation, supporting environmentally responsible farming.